Economies of size for Kansas beef cow production - Michael R. Langemeier; Ted C. Schroeder (Kansas Agricultural Experiment Station Research Reports, 1994)
Economies of size measure the impact of increasing the size of operation on average cost of production. Economies o f size exist if average total cost decreases as size increases. Enterprise data from producers enrolled in the Kansas Farm Management Associations in 1992 were used t o empirically estimate economies of size for beef cow enterprises. Results indicate that economies of size exist for beef cow enterprises. Average total cost per head declined as the number of beef cows increased. Substantial variability in costs of production between producers also were documented. Costs of production between producers of a given size varied considerably more than changes in cost of production attributed to size alone. Smaller than average beef cow enterprises can compete in the 1990's, if they are cost competitive. In addition to size, feed costs, fixed costs, production efficiency, and sale prices of calves were important factors affecting the profitability of beef cow enterprises.
Keywords: Cattlemen' s Day; 1994; Kansas Agricultural Experiment Station contribution; no. 94-373-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 704; Beef; Economies of size; Cost of production; Profitability; Cow/calf